Blood Pressure Increase and Microvascular Dysfunction Accelerate Arterial Stiffening in Children: Modulation by Physical Activity - Lona, Giulia; Hauser, Christoph; Köchli, Sabrina; Infanger, Denis; Endes, Katharina; Faude, Oliver; Hanssen, Henner (Frontiers in Physiology, 2020)
Background: Atherosclerotic remodeling starts early in life and can accelerate in the presence of 11 cardiovascular risk (CV) factors. Regular physical activity (PA) can mitigate development of large and 12 small artery disease during lifespan. We aimed to investigate the association of changes in body mass 13 index (BMI), blood pressure (BP), PA behavior and retinal microvascular diameters with large artery 14 pulse wave velocity (PWV) in prepubertal children over four years. 15 Methods: The school-based prospective cohort study included 262 children initially aged 6-8 years, 16 assessing the above CV risk factors and retinal vessels by standardized procedures at baseline (2014) 17 and follow-up (2018). PWV was assessed by an oscillometric device at follow-up. 18 Results: Children with increased systolic BP over four years showed higher PWV at follow-up (β [95% 19 CI] 0.006 [0.002 to 0.011] mmHg per unit, P=0.002). In contrast, increased vigorous PA corresponded 20 to a lower PWV at follow-up (β [95% CI] -0.009 [-0.018 to <0-.001] 10 min/d per unit, P=0.047). 21 Progression of retinal arteriolar narrowing and venular widening were linked to a higher PWV after 22 four years (β [95% CI] -0.014 [-0.023 to -0.004] 0.01 changes per unit, P=0.003). 23 Conclusions: Increase in systolic BP and progression of microvascular dysfunction were associated 24 with higher PWV after four years. Children with increasing levels of vigorous PA were found to have 25 lower PWV at follow-up. Habitual vigorous PA has the potential to decelerate the process of early 26 vascular ageing in children and may thus help counteract CV disease development later in life.